Enseñanza de discursos míticos para el desarrollo de la comprensión lectora de los estudiantes universitarios - Arrieta Espinoza, Dimas Nello (2022)
The objective of this research is to propose the teaching of mythical discourse as a strategy to develop reading comprehension in university students, considering that the culture reflected in myths contributes to cultural identity. 10 myths are presented. The work is pertinent given the need to develop the categories of reading competence in university students, who are dependent readers in basic informative, documentary and numerical texts and deficient in literary, humanistic and scientific texts.